Infant isoflurane exposure affects social behaviours, but does not impair specific cognitive domains in juvenile non-human primates. (February 2021) - Neudecker, Viola; Perez-Zoghbi, Jose F.; Coleman, Kristine; Neuringer, Martha; Robertson, Nicola; Bemis, Alexandra; Glickman, Bess; Schenning, Katie J.; Fair, Damien A.; Martin, Lauren D.; Dissen, Gregory A.; Brambrink, Ansgar M.
Abstract: Background: Clinical studies show that children exposed to anaesthetics for short times at young age perform normally on intelligence tests, but display altered social behaviours. In non-human primates (NHPs), infant anaesthesia exposure for several hours causes neurobehavioural impairments, including delayed motor reflex development and increased anxiety-related behaviours assessed by provoked response testing. However, the effects of anaesthesia on spontaneous social behaviours in juvenile NHPs have not been investigated. We hypothesised that multiple, but not single, 5 h isoflurane exposures in infant NHPs are associated with impairments in specific cognitive domains and altered social behaviours at juvenile age. Methods: Eight Rhesus macaques per group were anaesthetised for 5 h using isoflurane one (1×) or three (3×) times between postnatal days 6 and 12 or were exposed to room air (control). Cognitive testing, behavioural assessments in the home environment, and provoked response testing were performed during the first 2 yr of life. Results: The cognitive functions tested did not differ amongst groups. However, compared to controls, NHPs in the 3× group showed less close social behaviour ( P =0.016), and NHPs in the 1× group displayed increased anxiety-related behaviours ( P =0.038) and were more inhibited towards novel objects ( P <0.001). Conclusions: 5 h exposures of NHPs to isoflurane during infancy are associated with decreased close social behaviour after multiple exposures and more anxiety-related behaviours and increased behavioural inhibition after single exposure, but they do not affect the cognitive domains tested. Our findings are consistent with behavioural alterations in social settings reported in clinical studies, which may guide future research.